ANALYSIS OF VARIATION IN HEAT CONDUCTING PIPE POSITION AND AIR VELOCITY ON DRYING RATE, MOISTURE CONTENT AND DRYING EFFICIENCY OF TAPIOCA CRACKERS - Amriadi Amriadi; Mietra Anggara (Universitas Katolik Widya Karya Malang, 2023)
One of the essential processes in the production of krupuk (crackers) is the drying process, commonly carried out using traditional sun-drying methods. Effective drying necessitates even heat distribution, which can be challenging to achieve with direct sun drying due to weather fluctuations. However, with technological advancements, natural drying methods have been improved to enhance drying efficiency. Moreover, the development of drying equipment has shifted from natural drying to forced drying using the principle of fluidization. Experimental testing of the heat pipe position and air velocity can be conducted to understand the heat One of the essential processes in the production of krupuk (crackers) is the drying process, commonly carried out using traditional sun-drying methods. Effective drying necessitates even heat distribution, which can be challenging to achieve with direct sun drying due to weather fluctuations. However, with technological advancements, natural drying methods have been improved to enhance drying efficiency. Moreover, the development of drying equipment has shifted from natural drying to forced drying using the principle of fluidization. Experimental testing of the heat pipe position and air velocity can be conducted to understand the heat distribution during the drying process. The objective of this research is to investigate the variation of heat pipe positions and air velocities' influence on the drying rate, moisture content, and drying efficiency of krupuk. The study involves three research variables: Independent Variables: a. Designing the heat pipe in a vertical position. b. Designing the heat pipe in a horizontal position. Air Velocity: a. Air velocity of 2 m/s. b. Air velocity of 1.5 m/s. c. Air velocity of 1 m/s. Based on the comparison of values from the two positions, it was found that the vertical heat pipe resulted in the best drying rate of 1.65 g/minute, while the horizontal heat pipe yielded 1.67 g/minute. Regarding moisture content, the vertical heat pipe had a value of 3.6%, while the horizontal pipe had 2.6%. For the best efficiency, the vertical heat pipe achieved 1.9%, and the horizontal pipe achieved 2%. It can be concluded that the drying rate and moisture reduction significantly affect the efficiency of the kerupuk drying machine. The higher the quantity of material dried, the higher the efficiency achieved with the same fuel.